MUNASABAH IN THE PERSPECTIVE OF SCIENCE OF THE QUR'AN: STUDY OF AL-BURHAN FI ULUMUL QURAN WORKS OF AL-ZARKASYI (D. 749 H) - Mia Fitriah Elkarimah (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
Studying the munasabah of the Qur'an can be considered important, but in the development of the Qur'anic sciences, the science of munasabah of the Qur'an is a scientific discipline, sometimes it is studied, sometimes it is not. Because the issue of munasabah is included in the category of ijtihad, the rules are also ijtihadi. the legendary Egyptian cleric al-Zarkasyi is one of the oldest 'Ulum Al-Qur'an writers. Al-Burhan Fi 'Ulum Al-Qur'an is the eternal witness of his most monumental work. Although this book has been less popular since his death, but the presence of al Suyuthi, who lived about two centuries later, made this work shine again and became a famous work through al Itqan fi Ulum Al-Qur'an. This paper describes the munasabah from the book Al-Burhan Fi 'Ulum Al-Qur'an. This research model is entirely a literature study, in this case the primary data is the work of Master piece Al-Zarkasyi. Meanwhile, secondary data sources include other references written by intellectuals, either in the form of comments, analyzes or academic works. According to Al-Zarkasyi, munasabah is an attempt by human thought to explore the secret of the relationship between verses or letters that can be accepted by reason. He discussed Munasabah after discussing asbabul nuzul. In terms of its nature, munasabah can be divided into two types, Zahirul Irtibathi, and Khafi Irtibathi. While Munasabah can be in the form of amm-khash in one theme; relationships according to logical reasoning ('aqli), relationships according to sensory perception (hissi), relationships based on contemplation (khayyali). Or also munasabah in terms of cause and effect (illah-ma'lul/sabab-musabbab); comparison (tandhir) and opposite relationship (madladdah). Or the framework of external latent relationships (al-talazum al-khariji). There are two patterns of munasabah introduced by al-Zarkasyi in the book al-Burhan fi 'Ulum al-Qur'an. First, the pattern of discussion between letters and the second between verses. Mengkaji munasabah al-Qur’an dapat dianggap penting, tapi dalam perkembangan ilmu-ilmu Alquran, ilmu munâsabah Alquran merupakan disiplin ilmu kadang dikaji kadang tidak. Karena persoalan munasabah termasuk dalam kategori ijtihad, maka kaidah-kaidahnya pun bersifat ijtihadi. seorang ulama legendaris Mesir al-Zarkasyi merupakan salah satu penulis ‘Ulum Al-Qur’an tertua. Al-Burhan Fi ‘Ulum Al-Qur’an merupakan saksi abadi karyanya yang paling momumental. Meskipun kitab ini kurang populer sejak sepeninggalnya, namun kehadiran al Suyuthi, yang hidup sekitar dua abad sesudahnya, menjadikan karya ini kembali bersinar dan menjadi sebuah karya yang terkenal melalui al Itqan fi Ulum Al-Qur’an. Tulisan ini menggambarkan tentang munasabah dari kitab Al-Burhan Fi ‘Ulum Al-Qur’an. Model penelitian ini adalah sepenuhnya studi kepustakaan, dalam hal ini data primer adalah karya Master piece Al-Zarkasyi. Sedangkan Sumber data sekunder, mencakup referensi-referensi lain yang ditulis para intelektual, baik berupa komentar, analisa maupun karya-karya akademik. Menurut Al-Zarkasyi munasabah merupakan upaya pemikiran manusia untuk menggali rahasia hubungan antar ayat atau huruf yang dapat diterima akal. Ia membahas soal Munasabah sesudah membahas asbabul nuzul. Dari segi sifatnya munasabah dapat terbagi menjadi dua macam, Zahirul Irtibathi, dan Khafi Irtibathi. Sedangkan Munasabah dapat berupa amm-khash dalam satu tema; hubungan menurut penalaran logika (‘aqli), hubungan menurut pencerapan inderawi (hissi), hubungan berdasarkan kontemplasi (khayyali). Atau juga munasabah dalam kerangka sebab dan akibatnya (illah-ma’lul/sabab-musabbab); pembandingan (tandhir) dan hubungan berlawanan (madladdah). Atau kerangka hubungan laten eksternal (al-talazum al-khariji). Ada dua pola munasabah yang dikenalkan oleh al-Zarkasyi dalam kitab al- Burhan fi ‘Ulum al-Qur’an. Pertama, pola munasabah antar surat dan kedua munasabah antar ayat.